Utilization of cytochrome oxidase subunit 1 gene to investigate the giant freshwater prawn, Macrobrachium rosenbergii resources in Malaysia with a special focus on the southeast asian population phylogeny / Ayu Cera Lutas - Ayu Cera , Lutas (2018)
Productivity of Giant Malaysian Prawn (GMP) in 2013 to present has demonstrated a decrease in yield and survival that caused farmers to move to an easier crop, for example, tilapia and catfish, despite the fact that the demand of Giant Malaysian Prawn (GMP) is still high. Translocations of broodstocks for breeding purposes and restocking program from hatchery population to riverine systems could lead to loss of genetic diversity. By utilising mitochondrial DNA cytochrome oxidase subunit-1 (COI), we believe it can be a quick system, to assess genetic diversity in domesticated culture in farms from nine locations dispersed all through Peninsular Malaysia. AMOVA between wild and domesticated GMP showed that the genetic variation between these two groups was not significantly different, however, based on maximum-likelihood tree and Tajima’s D value Johor (wild stock) is unique and different from other populations. Domesticated populations, KKL, BLG and LGG populations have high genetic diversity, thus, these populations are suitable to become base population, instead of wild stocks, for genetic improvement program. The temporal analysis between two different time cohorts, 2004 and 2013, revealed that there was reduction of haplotype diversity and nucleotide diversity. This is supported with high FST value of Sg. Johor and Sg. Kedah between 2004 and 2013. Analysis between GMP from Malaysia with Southeast Asian countries revealed that the geographic origin location could be from Malaysia as haplotype 5, 14 and 31 were ancestral haplotype. These findings could show that mtDNA COI genetic marker, is useful to evaluate population genetic structure of the freshwater prawn in Malaysia, very quickly and helps to manage the stocks in a more sustainable manner.